PENGARUH MODEL PAIRED STORYTELLING BERBANTUAN MEDIA RUNNING STORY BOX (RUSBOX) TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V - Noorputri, Dita Estu; Anni Malihatul Hawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low level of students’ speaking skills. This study aims to determine the effect of the Paired Storytelling model assisted by the Running Story Box (Rusbox) media on students’ speaking skills. This research employed a quantitative approach using a quasi-experimental design in the form of a pretest–posttest design with random sampling. The sampling technique used in this study was purposive sampling. The research samples were students of classes VB and VC at SD Negeri Ungaran 01. The data collection techniques in this study included test techniques (pretest and posttest) and non-test techniques (observation, questionnaires, structured interviews, and documentation). The data analysis techniques consisted of a normality test, homogeneity test, independent samples t-test, and simple linear regression test. The results of the study indicate that: (1) there is a difference in students’ speaking skills between those taught using the Paired Storytelling model assisted by the Running Story Box (Rusbox) media and those who were not, as evidenced by the results of the independent samples t-test with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted; and (2) there is an effect of the Paired Storytelling model assisted by the Running Story Box (Rusbox) media on students’ speaking skills, as evidenced by the results of the simple linear regression test with a significance value of 0.037 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Based on these findings, it can be concluded that the use of the Paired Storytelling model assisted by the Running Story Box (Rusbox) media has a significant effect on the speaking skills of fifth-grade students.